TRANSFORMASI DIGITAL PADA SISTEM KEARSIPAN DI SMAN 1 TAKENGON KABUPATEN ACEH TENGAH - Farid Fauzi; Royandi Irvansyah (Universitas Muhammadiyah Surakarta, 2022)
This research examines the implementation process of digital transformation in the archive system at SMAN 1 Takengon. The approach use in this research is descriptive quantitative by using survey techniques that support the results of this research. The unit of analysis in this study are staff and teacher with 57 population. Based on the results of the study, there was an implementation of digital transformation that was still not stable and there was a combination system between an archival system that was still manual and digital. This was done because the digital archiving system at SMAN 1 Takengon worked as a data backup on the manual archived system. Based on the results of research in the field, it could be guaranteed that the implementation of digital transformation in the archival system at SMAN 1 Takengon has not been implemented completely from the process in the archive system at SMAN 1 Takengon.